UPACARA KEAGAMAAN DALAM PERSPEKTIF PRILAKU DAN EKONOMI - I Made Olas Astawa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Religious ceremonies in the view of Hinduism as a form of sacrifice to Hyang Widhi,Pitra, Rsi, Humans and the surrounding world, known as Panca Yadnya. Religious ceremonieshave at least four meanings; namely (1) efforts to purify the mind towards clear, wise and wise;(2) the concrete realization of Panca Sradha; (3) realization of the willingness of Hindus to make sacrifices; and (4) forms of expression of gratitude for all of His gifts (both to Hyang Widhi, ncestors and Rsi) and at the same time as concrete expressions of the behavior of Hindus about Tri Ram. Yajna (religious ceremony) is the expression of concrete and observable behavior. Sociologically religious ceremonies are important phenomena in order to understand the various symbols used by the ceremony, and repeatedly, in addition to functioning as a means of channelingreligious emotion, it is also the driving force of the emotion and ultimately affects the behavior of the followers of the religion. Religious ceremonies as concrete expressions and the concept of Tri Ram places humans according to Hinduism as creatures owing to Hyang Widhi (Dewa Ram), debts to Ancestors and Parents (Pitra Ram) and debts to Rsi (Rsi Ram). Besides that, religious ceremonies play a role in shaping Hindu behavior such as solidarity, rationality, creativity,ethical hard work, solidarity and social care. Apart from that religious ceremonies can encourage two very important things; firstly, religious ceremonies became a spiritual-religious force in the formation of the visionary behavior of Hindus in Bali, both religious ceremonies became religious spiritual forces as economic drivers in the form of increased per capita, business opportunities, and employment opportunities.